Rv0100, a proposed acyl carrier protein in Mycobacterium tuberculosis: expression, purification and crystallization. Corrigendum. Issue 4 (7th April 2020) - Bondoc, Jasper Marc G.; Gutka, Hiten J.; Almutairi, Mashal M.; Patwell, Ryan; Rutter, Maxwell W.; Wolf, Nina M.; Samudrala, Ram; Mehboob, Shahila; Dementiev, Alexey; Abad-Zapatero, Cele; Movahedzadeh, Farahnaz
Abstract : A correction is made to the article by Bondoc et al. [(2019). Acta Cryst. F75, 646–651] . Abstract : The true identity of the protein found in the crystals reported by Bondoc et al. [(2019), Acta Cryst. F75, 646–651] is given.